2003
DOI: 10.1007/s00213-002-1372-z
|View full text |Cite
|
Sign up to set email alerts
|

Effect of treatment status on prepulse inhibition of acoustic startle in schizophrenia

Abstract: Our results do not support the hypothesis that impaired sensorimotor gating in schizophrenia improves with antipsychotic treatment. Rather, impaired gating persists despite symptomatic improvement on medication.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
34
1
1

Year Published

2003
2003
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(39 citation statements)
references
References 33 publications
3
34
1
1
Order By: Relevance
“…In contrast to clozapine, Duncan et al (2003a) found that patients treated with olanzapine had levels of PPI comparable to patients treated with haloperidol or patients who are not treated at all, whereas this group as a whole showed significantly less PPI compared with healthy controls. This indicates that not every atypical antipsychotic is capable of normalizing PPI deficits, which also seems to be confirmed by a similar study of this group (Duncan et al, 2003b). In addition, in a recent study by Kumari et al (2006), patients treated with olanzapine and risperidone showed levels of PPI that were not significantly different from either healthy controls or from patients treated with typical antipsychotics (who showed significantly less PPI than the healthy controls).…”
Section: Introductionsupporting
confidence: 69%
“…In contrast to clozapine, Duncan et al (2003a) found that patients treated with olanzapine had levels of PPI comparable to patients treated with haloperidol or patients who are not treated at all, whereas this group as a whole showed significantly less PPI compared with healthy controls. This indicates that not every atypical antipsychotic is capable of normalizing PPI deficits, which also seems to be confirmed by a similar study of this group (Duncan et al, 2003b). In addition, in a recent study by Kumari et al (2006), patients treated with olanzapine and risperidone showed levels of PPI that were not significantly different from either healthy controls or from patients treated with typical antipsychotics (who showed significantly less PPI than the healthy controls).…”
Section: Introductionsupporting
confidence: 69%
“…ANCOVA with the baseline startle amplitude serving as the covariate seems an obvious solution to take into account of startle difference between groups (Aasen et al 2005;Duncan et al 2003;Frankland et al 2004;Vollenweider et al 2006;Weike et al 2000;Yee et al 2004). However, the use of ANCOVA for this purpose may not be entirely appropriate:…”
Section: Baseline Startle Reaction As a Covariate: The Use Of Ancova mentioning
confidence: 99%
“…Duncan and colleagues (2003) tested unmedicated, de-compensated schizophrenia patients and retested them 3 months after antipsychotic treatment (Duncan et al, 2003). They found continued impaired PPI in the face of symptomatic improvement; however, this study did not include a non-schizophrenia comparison group, limiting the ability to draw definitive conclusions.…”
Section: Introductionmentioning
confidence: 99%